PENGEMBANGAN MODEL KURIKULUM PENDIDIKAN AGAMA ISLAM BERBASIS KEARIFAN LOKAL UNTUK SEKOLAH MENENGAH DI WILAYAH PEDESAAN - Hasyim As'Ari (UNISAN JURNAL, 2024)
Development of an Islamic Religious Education Curriculum Model Based on Local Wisdom for Middle Schools in Rural Areas is a research that aims to formulate a curriculum model that integrates Islamic religious values with local wisdom that exists in rural areas of Indonesia. Through a qualitative approach involving literature study, primary data collection, and thematic analysis, this research succeeded in producing a curriculum model that is relevant, contextual, and can be applied effectively in the field. This curriculum model emphasizes the importance of extracurricular activities that prioritize local wisdom, such as mutual cooperation activities, learning to make batik, and getting to know the natural surroundings, as a means of strengthening students' religious identity and strengthening the cultural values that are characteristic of rural areas. By involving various related parties, including community leaders, ulama, religious teachers, parents of students, and local government, this curriculum model is expected to meet the needs and expectations of society and create a young generation who not only have faith, but also have a strong connection to values. -their cultural values and local wisdom. The implementation of this curriculum model is expected to make a significant contribution in improving the quality of Islamic religious education in rural areas, creating education that is more inclusive, relevant and globally competitive.